2009
DOI: 10.1080/00207450802572188
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mirror Neurons in Processing Vocal Emotions: Evidence from Psychophysiological Data

Abstract: Recent evidence suggests that the mirror neuron system may serve as a common neural substrate for processing motor, linguistic, emotional, and other higher-level cognitive information. The current study employed psychophysiological methods to elucidate the role of this system in processing vocal emotions. Skin conductance and heart rate were measured for 25 undergraduate students while they were both listening to emotional vocalizations and also thinking (internal production) about them. The results revealed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Recent literature has shown that the brain’s mirror neuron system is strongly involved in motoric imitation as well as in vocal imitation, a phenomenon first investigated in song birds (Prather, 2013) that learn their melody lines by imitation. On the basis of various neuroimaging studies, the claim could be made that the intertwined involvement of receptive and expressive functions, especially during vocal production, is a sign of a refined learning system of human social communication (Brown et al, 2004; Ramachandra et al, 2009; Leveque et al, 2013). Recent findings discussed the underlying pathways for vocal and non-vocal perception and production (Loui et al, 2009) which could be interpreted as a reason for a potentially different outcome for instrumental versus vocal imitation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has shown that the brain’s mirror neuron system is strongly involved in motoric imitation as well as in vocal imitation, a phenomenon first investigated in song birds (Prather, 2013) that learn their melody lines by imitation. On the basis of various neuroimaging studies, the claim could be made that the intertwined involvement of receptive and expressive functions, especially during vocal production, is a sign of a refined learning system of human social communication (Brown et al, 2004; Ramachandra et al, 2009; Leveque et al, 2013). Recent findings discussed the underlying pathways for vocal and non-vocal perception and production (Loui et al, 2009) which could be interpreted as a reason for a potentially different outcome for instrumental versus vocal imitation.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Ramachandra et al [14] physiological reactions to emotional words were tested in 25 undergraduate student participants [14]. These participants were comprised of eight men and 17 women with a mean age of 21.5 years.…”
Section: Emotional Primingmentioning
confidence: 99%
“…This may point towards the fact that the mirror neuron system is activated in both thinking about emotion, as one would through empathy, and during vocalization of emotion. The study by Ramachandra [14] and his colleagues reference recent studies [15][16][17][18] using both neuroimaging and electrophysiological testing procedures, reveal that specialized sets of neurons, specifically the mirror neuron system are implicated not only in the perception and imitation of action, but include cognitive and emotional functions as well as motor functions.…”
Section: Emotional Primingmentioning
confidence: 99%
See 2 more Smart Citations